Performance Evaluation Of Online Education Management During Covid-19 Situation In Bangladesh - Iftekhar Arif, Md.; Shahidul Islam, Md.; Md. Shahnur Azad Chowdhury, Dr.; Jonaed Kabir, Mohammad (International Journal of Educational Research & Social Sciences, 2023)
The physical education system collapse during the Covid-19 situation in Bangladesh and then online education was becoming popular to overcome the problem. The present study is conducted to measure the effect of online education in Covid-19 situation and the performance of the education system. The educational material, teaching facility and skill, online connection service, student acceptability, social acceptability and digital learning perception are identified as the main factor that influence online education, which are measured as (each five) close ended survey (five point Likert scale) questionnaire. The 400 survey response data are finalized by purposefully sampling in randomized block design from public and private university teachers of different division of Bangladesh and analyzed by descriptive analysis, Kolmogorov–Smirnov test, Shapiro –Wilk test, One-Sample Wilcoxon Signed Rank Test, Spearman's rho correlation, Mann–Whitney test, Kruskal–Wallis H test and ordinal logistic regression model by MS Excel 2016 and IBM SPSS Statistics 26 software. The result shows academic performance of online education, online educational material, online teaching facility and skill, online connection service, online student acceptability, online social acceptability and online digital learning perception are significantly higher than the median test value 3, which are significantly increasing during Covid-19 situation. It is observed that the quality of educational material, teaching facility and skill are significantly affect the academic performance of online education. But online connection service, student acceptability and social acceptability have no significant effect on the academic performance of online education. Also digital learning perception is significantly affect the academic performance of online education. It is observed from the study that the contribution of both male and female gender to the academic performance of online education are same, which are significantly higher perception from the median test value 3. The perception of private university is significantly higher than public university in the academic performance of online education, which are significantly higher perception from the median value. The perception of lower experience group has significantly higher perception on the academic performance of online education gradually. So, the experience of this study may be utilized in the planning and implementing online education management in Bangladesh.